Teachers Professional Identity and Its Influence On Quality Educational Outcomes in Kenya - Margaret Gathondu; Josphat Kagema; Anne Wanderi (STAI Miftahul Ula Nganjuk, 2020)
Quality education outcomes are the driving force of social developments. This has been the call and stipulations of various national and international frameworks including sustainable educational goals and Kenya’s vision 2030. Teachers are considered focal in providing quality education. Nevertheless, an examination of their pedagogical practices reveals gaps in the achievement of quality education outcomes. This study examined how teachers’ professional identity influences their pedagogical practices thereby impacting quality educational outcomes in Kenya and guided by the Attribution Theory. The focal research instruments used were questionnaires for teachers and learners in the selected public secondary schools in Nyeri and Laikipia County. Additionally, an interview guide was used to collect qualitative data from principals. Validity enhanced by the piloting of instruments prior to collecting the final data. Drawing from data of 400 secondary school teachers spread in two counties of Kenya, the study hypothesized that there was a significant difference set at p < .05 to assess if teachers’ professional identity influences quality education outcomes. To test the significance of this relationship, a one-way analysis of variance with a 0.05 level of significance was computed. The results clearly indicated a significant relationship between the teachers’ professional identity and teachers’ professional identity (F= 2.100, p=0.286). The study findings indicate that teachers have a pivotal role to play in quality education outcomes. It is the teacher who constructs the pillars of nation-building in the form of students’ development. It is the responsibility of teachers to train individuals’ different aspects of personality. For effective teaching-learning processes, the competent teacher is considered as a key. The study recommends that the school administration should make it possible to develop cooperation between parents and teachers for the sake of effective learning of students.